"Tablo" i filmska slika Roya Anderssona - Tomić, Janica (2014)
The paper examines the meanings of tableau in film history and in other media. Following its dominance during the so called primitive period of early cinema, tableau assumes the function of a stylistic alternative in a number of theories that have articulated its otherness in film history (Burch, Bordwell, Heath, Bazin, Michelson), referring to connotations of static image, anachronism, intermediality etc. Comparisons are drawn with descriptions of tableau in photography, literature and performative arts. Recent proliferation of theoretical discourse on tableau-effects found in a number of stylistically varied films (Bordwell, Bal, Dalle Vacche, Peucker) serves as a starting point for an analysis that further explorers the formal and affective qualities of cinematic tableaux. Combined with Deleuze's and other theoretical accounts of extreme depth of field and expressionism, a theoretical framework is established for an analysis of Roy Andersson’s films, particularly Songs from the second floor (2000), where, as the paper argues, tableau aesthetics realizes its utmost radical potential for transfiguring cinematic time and space.
HRV